PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP PERSEPSI MATEMATIKA SISWA - Susilo, Bangun; Ernawati, Agustin (Jurnal Pembelajaran Matematika, 2018)
Abstract:Mathematics is the prominent field of all scientific disciplines. Mathematics also has many benefits for human life. However, students' knowledge about benefits of learning mathematics for human life is still not reflected in students’ attitude during their mathematics learning. The students’ attitude in following mathematics learning is strongly influenced by students' perceptions of mathematics. A good perception will foster a positive attitude and vice versa, a bad perception will lead to negative one. One aspect that can affect students’ perceptions is learning model applied by a teacher. This study aims to determine the effect of cooperative learning model of Teams Games Tournament (TGT) type on students' perceptions. The research method is quantitative with One Group Pretest-Posttest Design. Data collection techniques use experiments and direct observation, while the instruments are questionnaires about students' mathematics perceptions. Data analysis is t-test from pretest and posttest data. Based on the results of t-test analysis, it is found that , which is5.71 ( ) and 2.16( ) with a significant level . Based on these results, it can be concluded that cooperative learning model of the TGT type influences students' mathematics perception.Keywords:Perception, Students’ Mathematics Perception, Teams Games Tournament.